Effect of Recombinant DNA-produced Bovine Interferon Alpha (BoIFN-α1) on the Interaction between Bovine Alveolar Macrophages and Bovine Herpesvirus Type 1 - Ohmann, H. Bielefeldt; Gilchrist, J. E.; Babiuk, L. A. (Journal of General Virology, 1984)
SUMMARY Treatment of bovine alveolar macrophages (BAM) with bovine leukocyte interferon (BoIFN-α1) resulted in reduced bovine herpesvirus type 1 replication and spread. This was demonstrated by reduced virus yields and number of cells infected. BoIFN-α1 treatment of BAM also induced enhanced Fc receptor expression and/or avidity by the cells, increased their activity in antibody-dependent cellular cytotoxicity, and augmented their extrinsic antiviral activity as measured by a reduction in the development of plaques in a susceptible cell line. These results are discussed in the context of the possible role of interferon in activation of AM during the early phases of a virus infection.
Keywords: BHV-1